2019
DOI: 10.1038/s41598-019-44591-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined Amylin/GLP-1 pharmacotherapy to promote and sustain long-lasting weight loss

Abstract: A growing appreciation of the overlapping neuroendocrine mechanisms controlling energy balance has highlighted combination therapies as a promising strategy to enhance sustained weight loss. Here, we investigated whether amylin- and glucagon-like-peptide-1 (GLP-1)-based combination therapies produce greater food intake- and body weight-suppressive effects compared to monotherapies in both lean and diet-induced obese (DIO) rats. In chow-maintained rats, systemic amylin and GLP-1 combine to reduce meal size. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 72 publications
(99 reference statements)
2
21
0
2
Order By: Relevance
“…During OGTT, both short and longterm treatment with KBP-089 improved glucose tolerance in accordance with previous studies performed with KBP-089 (Gydesen, Andreassen, et al, 2017;. Interestingly, the effect on blood glucose during OGTT was especially pronounced in combination therapy groups, particularly after eight weeks of treatment, supporting that the peptides act though complimentary pathways, and possibly that the combination leads to increased durability of the glucoregulatory effects compared to stand-alone treatment, consistent with the study by Liberini et al (2019). Importantly, along with improved glucose clearance, signi cantly lower insulin levels during OGTT were observed in KBP-089 (1.25 and 2.5 µg/kg) and combination therapy groups, indicating improved insulin sensitivity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…During OGTT, both short and longterm treatment with KBP-089 improved glucose tolerance in accordance with previous studies performed with KBP-089 (Gydesen, Andreassen, et al, 2017;. Interestingly, the effect on blood glucose during OGTT was especially pronounced in combination therapy groups, particularly after eight weeks of treatment, supporting that the peptides act though complimentary pathways, and possibly that the combination leads to increased durability of the glucoregulatory effects compared to stand-alone treatment, consistent with the study by Liberini et al (2019). Importantly, along with improved glucose clearance, signi cantly lower insulin levels during OGTT were observed in KBP-089 (1.25 and 2.5 µg/kg) and combination therapy groups, indicating improved insulin sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…the dorsal-vagal-complex (DVC), which contains the area postrema and the nucleus tractus solitarius (Liberini et al, 2019). These studies showed a combined effect of SCT and liraglutide on c-fos activation in the DVC, consistent with a combined suppression of food intake and gastric emptying (Liberini et al, 2019;. Furthermore, earlier work indicated that this effect may entail a local upregulation of brain IL-6 in the hypothalamus, by both amylin and GLP-1 (Jansson and Palsdottir, 2015).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The inhibited gastric emptying can positively affect postprandial blood glucose levels by delaying entry of glucose into circulation, a central factor in diabetes treatment. From a mechanistic point-of-view, a series of studies have looked into co-administration of either amylin or the DACRA salmon calcitonin (SCT) in combination with incretin-based therapies [ 4 , 12 , 28 ]. These studies have highlighted that both amylin and GLP-1 activate receptors in the same areas of the hind brain, i.e.…”
Section: Discussionmentioning
confidence: 99%